Tantangan Pendidikan IPS di Era Globalisasi - Annur Rosida Siregar; Emilia Susanti; Irma Fitriani; Nurul Annisah; Nanda Lubis; Aldi Juliaska (Universitas 45 Surabaya, 2024)
Global issues can capture the attention of the international community and have widespread impacts, motivating groups to make bold decisions. Participants in social sciences play a key role in fostering responsible citizenship, which enables them to effectively address global issues through more meaningful learning, thereby reducing the negative effects of these issues. Social Studies entails the simplification and selection of disciplines within the social sciences and humanities, as well as fundamental human activities, organized and presented scientifically and psychologically for educational purposes. Implementing Social Studies education is challenged by global issues. To tackle these challenges, efforts are required at both organizational and classroom levels. Institutionally, the Social Studies curriculum must be adapted to address global challenges, and the frequency and quality of academic forums should be increased. In the classroom, teachers and instructors must enhance their skills through training and creativity to deliver meaningful learning and contribute to the development of good citizens.